The clinical and laboratory manifestations of Iranian patients with cystic fibrosis - Fallahi, Gholamhossein; Najafi, Mehri; Farhmand, Fatemeh; Bazvand, Fatemeh; Ahmadi, Maedeh; Ahmadi, Faezeh; Eftekhari, Kambiz; Khodad, Ahmad; Motamed, Farzaneh; Khatami, Gholamreza; Aghamohammadi, Asghar; Rezaei, Nima (The Turkish Journal of Pediatrics, 2010)
Cystic fibrosis (CF) is a hereditary disease, characterized by chronic pulmonary disease, pancreatic insufficiency and abnormal electrolytes in the sweat. In order to evaluate the clinical manifestations and laboratory findings of Iranian children with CF during a 10-year period, 243 CF patients, with a median age of 5 months, were investigated in this study. The most common manifestations were gastrointestinal disorders and respiratory manifestations. Cough was the most common symptom, followed by malnutrition, diarrhea, respiratory distress, and vomiting. The frequency of these findings after treatment was significantly decreased in comparison with the period before diagnosis. During the mean follow-up of 40.9 months, seven cases died due to severe infections. Cystic fibrosis as a common genetic disorder should be considered in any child with recurrent gastrointestinal and respiratory manifestations, since delayed diagnosis could lead to severe complications and even death in this group of patients.